Glas Maol microresp data 2009 - Wubs, E. R. Jasper; Woodin, Sarah J.; Stutter, Marc I.; Wipf, Sonja; Sommerkorn, Martin; Van Der Wal, René (Dryad Digital Repository, 2018)
This file contains the measured SIR rates of the microresp analysis on all of the experimental field plots.